Organophosphorus flame retardants and plasticizers: Sources, occurrence, toxicity and human exposure - Wei, Gao-Ling; Li, Ding-Qiang; Zhuo, Mu-Ning; Liao, Yi-Shan; Xie, Zhen-Yue; Guo, Tai-Long; Li, Jun-Jie; Zhang, Si-Yi; Liang, Zhi-Quan (Environmental pollution (1987), 2015)
Due to the restricted use and ban of brominated flame retardants, organophosphorus compounds (OPs), extensively used as flame retardants and plasticizers, are ubiquitous in various environmental compartments worldwide. The present study shows that the release of OPs from a wide variety of commercial products and wastewater discharge might be considered as primary emission sources and that high potential of long-range atmospheric transport and persistence of OPs would be responsible for their presence in various matrices on a global scale. The occurrence and environmental behaviors of OPs in diverse matrices (e.g., dust, air, water, sediment, soil and biota) are reviewed. Human exposures to OPs via dermal contact, dust ingestion, inhalation and dietary intake are comprehensively evaluated. Finally, this study identifies gaps in the existing issues and generates a future agenda for the emerging contaminants OPs. [Display omitted] •Organophosphorus compounds (OPs) are ubiquitous in various environmental matrices worldwide.•Release of OPs from products and wastewater discharge are treated as primary emission sources.•High potentials of LRAT and persistence of OPs account for their global occurrence.•Dust intake is more important than inhalation and food intake for human, especially for toddlers.•Research gaps are concluded to define the directions and the primary emphasis of future studies. The emission sources, environmental occurrence, toxicity and human exposure of organophosphorus flame retardants and plasticizers are fully reviewed.